2019
DOI: 10.1016/j.jcs.2019.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the nutritional profile of sweet maize after herbicide and foliar fertilizer application

Abstract: Intensive weed management is required to meet the growing demands of sweet maize production. Herbicide application is inevitable in sweet maize production, while foliar fertilizer is commonly used in cropping in order to improve crop yield and quality. The effect of nicosulfuron and mesotrione, with and without foliar fertilizer, on the content of phytochemicals (i.e. carotenoids, tocopherols and free phenolic acids) in the kernels of three sweet maize hybrids was evaluated. Herbicides applied alone mainly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 28 publications
(41 reference statements)
1
11
0
Order By: Relevance
“…Previous research has shown that mulches (foils) expressed positive impact on total sugar accumulation, while the highest concentration of vitamin C was in kernel of sweet maize that was grown uncovered [39]. It was also established that some cropping practices, like fertilization, and herbicide application [40] could affect carotenoids level in sweet maize kernel, but data about CC influence on carotenoids accumulation in sweet maize kernel are still unknown. In this research, concentration of YP, as another promoter, varied mainly under the influence of fodder kale (T4) and common vetch + winter oats + BF (T5 + BF), indicating that larger amount of organic residues (present after incorporation), resulted in increased amount of available N in soil [7,11], thus affecting positively the yield YP accumulation in kernels of sweet maize.…”
Section: Potential Bio-availability Of Essential Elementsmentioning
confidence: 99%
“…Previous research has shown that mulches (foils) expressed positive impact on total sugar accumulation, while the highest concentration of vitamin C was in kernel of sweet maize that was grown uncovered [39]. It was also established that some cropping practices, like fertilization, and herbicide application [40] could affect carotenoids level in sweet maize kernel, but data about CC influence on carotenoids accumulation in sweet maize kernel are still unknown. In this research, concentration of YP, as another promoter, varied mainly under the influence of fodder kale (T4) and common vetch + winter oats + BF (T5 + BF), indicating that larger amount of organic residues (present after incorporation), resulted in increased amount of available N in soil [7,11], thus affecting positively the yield YP accumulation in kernels of sweet maize.…”
Section: Potential Bio-availability Of Essential Elementsmentioning
confidence: 99%
“…The contents of proteins, oil and starch were determined with an NIR analyser Infraneo (Chopin, France). Then, grains were milled (particle size < 500 µm) using a laboratory mill SJ 500 (MetronGroup, Novi Sad, Serbia) and the concentrations of carotenoids (lutein, zeaxanthin and β-carotene) and tocopherols (α-T, β+γ-T, δ-T) were determined by HPLC (Dionex UltiMate 3000 liquid chromatography system-Thermo Scientific, Germany) by the method proposed by Mesarović et al [28]. The content of carotenoids was expressed as a sum of concentrations of lutein, zeaxanthin and β-carotene.…”
Section: Sampling and Analysismentioning
confidence: 99%
“…Therefore, sweet corn is recognized as quality and delicious food. The content of those phytochemicals is highly influenced by the genotype and also by applied agricultural (Mesarović et al, 2019).…”
Section: Introductionmentioning
confidence: 99%